A LITERATURE STUDY ON THE INTONATION OF COLLOQUIAL INDONESIAN - Hana Nurul Hasanah (ETNOLINGUAL, 2018)
Standard Indonesian is the high variety used primarily in writings and formal occasions. On the other hand, the commonly used variety by Indonesian is Colloquial Indonesian. In addition, Colloquial Jakarta Indonesian is the most popular and influential amongst other variety used in daily conversation. Despite the important use of intonation to enhance communication, a comprehensive research towards Colloquial Jakarta Indonesian has rarely been done. This paper attempts to present and discuss research results concerning Indonesian Intonation and illustrate the general picture of colloquial Indonesian intonation. Considering the state-of-the-art findings in the previous research, this paper concludes the possible future investigations of Colloquial Indonesian intonation.Keywords:Intonation, colloquial Indonesian, literature review